2021
DOI: 10.21115/jbes.v13.n1.p49-54
|View full text |Cite
|
Sign up to set email alerts
|

Ensaio sobre a aderência ao modelo nacional de bengala eletrônica Smart Mobb® como recurso auxiliar à mobilidade de pessoas com cegueira ou baixa visão

Abstract: Objective: The objective of this work was to identify, through the questionnaire, favorable points and potentially impeding points for the purchase of Smart Mobb® as an auxiliary mobility technology for people with visual impairments. Methods: The questionnaire was applied at the Dorina Nowill Foundation for the Blind, an institution specialized in the care and rehabilitation of visually impaired people. The interview consisted of questions about the socioeconomic profile; Social; technological, in the context… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…A recent study by Rodrigues et al [26] found that implementing technological items would be a positive differential in the development of assistive technologies and that mobility is the greatest daily life difficulty faced by individuals with visual impairment. In a study with ten volunteers with visual impairment who used the long cane as an assistive technology for mobility, all of them showed interest in learning new assistive technologies for mobility; seven of them justified their choice due to the curiosity and the opportunity to improve their navigation skills [26,27].…”
Section: Joj Ophthalmologymentioning
confidence: 99%
“…A recent study by Rodrigues et al [26] found that implementing technological items would be a positive differential in the development of assistive technologies and that mobility is the greatest daily life difficulty faced by individuals with visual impairment. In a study with ten volunteers with visual impairment who used the long cane as an assistive technology for mobility, all of them showed interest in learning new assistive technologies for mobility; seven of them justified their choice due to the curiosity and the opportunity to improve their navigation skills [26,27].…”
Section: Joj Ophthalmologymentioning
confidence: 99%